2010
DOI: 10.1021/am900695a
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion Polymerization of Methyl Acrylate in Nonpolar Solvent Stabilized by Block Copolymers Formed In situ via the RAFT Process

Abstract: The free-radical dispersion polymerization of methyl acrylate (MA) in isododecane was carried out in the presence of a poly(2-ethylhexyl acrylate) macromolecular RAFT (reversible addition-fragmentation chain transfer) agent bearing a trithiocarbonate reactive group in the middle of the chain (P2EHA-TTC). The presence of the trithiocarbonate function was crucial for the synthesis of monodisperse colloidal poly(methyl acrylate) (PMA) particles stabilized by the P2EHA segments. The hydrodynamic diameters ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 36 publications
0
82
0
Order By: Relevance
“…[267] Pressley et al [611] have reported on an improved methodology for conducting click reactions to form block and cyclic polymers. [227] PFPMA/LMA Ph AIBN 25 70 100 [225] BA Ph AIBN 30 80 ,25 [194] HA Ph ACPA 5 70 100 [240] HA Ph AHPN 5 70 100 [240] BA/NA Ph AIBN 20 80 100 [202] BA C 4 H 9 S AIBN 30 80 ,25 [194] BA C 4 H 9 S AIBN þ BPO 20 þ 2 E 80 100 [194] HPA [596] tBA Poly(tBA)S AIBN -80 100 [597] NIPAm Poly(tBA-b-NIPAm)S AIBN -80 100 [597] tBA/TBBPMA Ph AIBN (20) (80) 100 [598] DAMEA/TFEA C 12 H 25 S AIBN 20 65 100 [599] HADA [194] St Ph AIBN þ BPO 20 þ 2 E 80 100 [194] St C 4 H 9 S AIBN 30 À 100 80 ,60 [194] St C 12 H 25 S AIBN 10 95 92 [393] A Monomer unit adjacent to thiocarbonylthio group. The process makes use of commercially available copper nanoparticles and is performed with microwave irradiation.…”
Section: Click Reactionsmentioning
confidence: 99%
“…[267] Pressley et al [611] have reported on an improved methodology for conducting click reactions to form block and cyclic polymers. [227] PFPMA/LMA Ph AIBN 25 70 100 [225] BA Ph AIBN 30 80 ,25 [194] HA Ph ACPA 5 70 100 [240] HA Ph AHPN 5 70 100 [240] BA/NA Ph AIBN 20 80 100 [202] BA C 4 H 9 S AIBN 30 80 ,25 [194] BA C 4 H 9 S AIBN þ BPO 20 þ 2 E 80 100 [194] HPA [596] tBA Poly(tBA)S AIBN -80 100 [597] NIPAm Poly(tBA-b-NIPAm)S AIBN -80 100 [597] tBA/TBBPMA Ph AIBN (20) (80) 100 [598] DAMEA/TFEA C 12 H 25 S AIBN 20 65 100 [599] HADA [194] St Ph AIBN þ BPO 20 þ 2 E 80 100 [194] St C 4 H 9 S AIBN 30 À 100 80 ,60 [194] St C 12 H 25 S AIBN 10 95 92 [393] A Monomer unit adjacent to thiocarbonylthio group. The process makes use of commercially available copper nanoparticles and is performed with microwave irradiation.…”
Section: Click Reactionsmentioning
confidence: 99%
“…Compared to RAFT alcoholic dispersion polymerization, there are relatively few reports of RAFT dispersion polymerization being conducted in non-polar solvents [92][93][94][95][96][97][98][99]. Charleux and co-workers [92][93][94] reported an all-acrylic RAFT non-polar dispersion polymerization formulation that produced poly(2-ethylhexyl acrylate)-poly(methyl acrylate) (PEHA-PMA) diblock copolymer nanoparticles in iso-dodecane.…”
Section: Raft Non-polar Dispersion Polymerizationmentioning
confidence: 99%
“…Charleux and co-workers [92][93][94] reported an all-acrylic RAFT non-polar dispersion polymerization formulation that produced poly(2-ethylhexyl acrylate)-poly(methyl acrylate) (PEHA-PMA) diblock copolymer nanoparticles in iso-dodecane. However, it is emphasized that only spherical nanoparticles could be accessed in this study.…”
Section: Raft Non-polar Dispersion Polymerizationmentioning
confidence: 99%
“…These authors demonstrated that presence of the RAFT agent on the stabilizer chain was crucial to allow for covalent grafting and thus efficient colloidal particle stabilization; the non-reactive P2EHA was unable to absorb onto the particle surface. [78] In addition, a kinetic study of the free radical polymerization in the presence of P2EHA-TTC and P2EHA-DTB showed that only the P2EHA-TTC stabilizer was able to control the polymerization leading to welldefined triblock copolymers forming small monodisperse core-shell colloidal particles (120 to 320 nm). [77,78] The use of P2EHA-DTB macro-RAFT agent as stabilizer at the lowest concentration did not provide control over the polymer structure (PDI =18) but led to the formation of small monodisperse particles (39 to 93 nm).…”
Section: Recent Progress In Stabilizer Designmentioning
confidence: 99%
“…[78] In addition, a kinetic study of the free radical polymerization in the presence of P2EHA-TTC and P2EHA-DTB showed that only the P2EHA-TTC stabilizer was able to control the polymerization leading to welldefined triblock copolymers forming small monodisperse core-shell colloidal particles (120 to 320 nm). [77,78] The use of P2EHA-DTB macro-RAFT agent as stabilizer at the lowest concentration did not provide control over the polymer structure (PDI =18) but led to the formation of small monodisperse particles (39 to 93 nm). However, the monomer conversion stayed low compared to the other macro-RAFT agent and an important retardation phenomenon was observed.…”
Section: Recent Progress In Stabilizer Designmentioning
confidence: 99%